Unleashing the Power of Oxygen-Doped Graphitic Carbon Nitride: Enhancing Neutral Red Removal Efficiency - Tamyiz, Muchammad; Annafis, Maulana Ahmad; Dhafa, Ahza Refkyan; Bulloh, Muhammad Basir Chis; Pisal, Mohd Hanif Mohd (Universitas Diponegoro, 2025)
Textile industry wastewater often contains persistent pollutants like neutral red dye, which are challenging to break down and harmful to ecosystems. This study introduces oxygen-doped graphitic carbon nitride (O-g-C3N4) as a photocatalyst to degrade neutral red dye under visible light. Synthesized using a single-step calcination of urea, dicyandiamide, and oxalic acid, O- g-C3N4 was tested for its efficiency in neutral red removal through adsorption and photocatalytic degradation, both in light and dark conditions. Results showed that O- g-C3N4 quickly adsorbed the dye, reaching equilibrium in 30 minutes and achieving a maximum adsorption capacity of 1.86 mg g-1, surpassing bulk g-C3N4. Kinetic analysis indicated that adsorption followed a pseudo-second-order model, suggesting chemisorption as the primary mechanism. Under visible light, O- g-C3N4’s photocatalytic degradation reached 86% neutral red removal, compared to 51% with bulk g-C3N4, largely due to improved light absorption and reduced electron-hole recombination. Degradation of neutral red followed pseudo-first-order kinetics, with O- g-C3N4’s reaction rate three times greater than bulk g-C3N4. The Sips isotherm best fit the adsorption data, confirming heterogeneous active sites and multilayer adsorption. These findings highlight O- g-C3N4’s potential for environmental remediation.